Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.

- anonymous

Evaluate 2xy - m when x = -4, y = 3, and m = 6 please show your work i dont know how to do this and this is worth 10 percent of my grade if i fail i will fail math please help me:(

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions.

Get your **free** account and access **expert** answers to this and **thousands** of other questions

- anonymous

- chestercat

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- whpalmer4

It is simple matching of numbers and letters, followed by arithmetic.
\[x=-4\]\[y=3\]\[m=6\]
Now take the equation and replace the letters with the corresponding numbers:
\[2xy-m = 2(-4)(3)-(6)\]
What does that equal?

- anonymous

i dont get it can u please show exaple?

- whpalmer4

I did. All you have to do is the arithmetic. What is
2*(-4)*3 - 6 ?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

- anonymous

-2?

- whpalmer4

What is 2*(-4)?

- anonymous

-2?

- whpalmer4

What is 2*4?

- anonymous

8?

- whpalmer4

Yes, 2*4 = 8. 2*(-4) = -8, because a positive number (2) times a negative number (-4) gives you a negative result (-8). A negative number times a negative number gives you a positive result, and of course a positive number times a positive number also gives you a positive result.
So, we've gotten the first multiplication done:
\[2*(-4)*3 - 6 = (-8)*3 - 6\]
What is (-8) * 3?

- anonymous

-22?

- anonymous

i mean -24

- whpalmer4

Yes. What is -24 - 6?

- anonymous

-28

- whpalmer4

Try again...

- whpalmer4

If you're at -24 on the number line, and you go 6 units to the left (subtracting 6 = moving 6 units to the left on the number line), where do you end up?

- anonymous

can u please just tell me this problem and teach me on the other one cuzz this is very importind and i need to put in befor 3:30:(

- whpalmer4

-24 - 6
what is 24 + 6? -24 -6 is the same thing, with a - sign in front...

- anonymous

31

- whpalmer4

4 + 6 = 10, doesn't it? So 24 + 6 = 20+10 = 30.
Similarly, -24 - 6 = -30

- anonymous

so its -30?

- anonymous

???

- whpalmer4

Yes...sorry, didn't notice you had responded.

- anonymous

now can u please right down the whole problmem in order done i wana see how it fully looks like

- whpalmer4

\[x=-4\]\[y=3\]\[m=6\]First substitute in value of \(x\):
\[2xy-m = 2(-4)y-m\]Now \(y\):
\[2xy-m = 2(-4)(3) -m \]Now \(m\):
\[2xy-m = 2(-4)(3) - (6)\]Do the arithmetic:
\[2xy-m = 2(-4)(3)-(6) = (-8)(3)-6 = -24 - 6 = -30\]

- anonymous

Before anything else you need to learn basic arithmetic, this is a elementary school skill. You should be able to add numbers under 100 together easily. For example:
58+12 = 70
70 - 30=40
39-11=28
11-12=-1
-2-45=-47
You NEED to be able to do this quickly and accurately. You can't add 24 and 6 and get 31... You need to think what 4+6 is...10! So how could the number end in 1?
From there the problem is asking to make a simple substitution. If I have:
a*b - c with a = 2, b = -3, and c = 4 then it's simply 2*(-3) - 4 = -6-4=-10.
Apply this to your current problem and any similar problem.

Looking for something else?

Not the answer you are looking for? Search for more explanations.